Mega arrowhead interference patterns in the central part of the Yanshan Orogenic Belt, North China. (November 2015) - Deng, Hongling; Koyi, Hemin A.
Abstract: The Chengde-Pingquan region is located in the central part of the Yanshan Orogenic Belt (YOB). At Daheishan and Pingquan in the central YOB, thrusts and folds of variable trends are displayed in 2 km-scale fold interference patterns. Detailed field mapping was conducted to decipher the geometry of these two superimposed structures. Map-view geometry and stereonet plots for outcrop-scale folds indicate that the superimposed structures form arrowhead interference pattern where NW-SE-trending F1 folds are refolded by later ENE-WSW F2 folding. After remove the effects of later faulting, restored map-views of the superimposed structures show that when the F1 folds have inclined axial surfaces but with no an overturned limb, an arrowhead interference pattern (here called modified type-2 pattern) can form. Our field data and reinterpretation of the findings of previous studies suggest that five major shortening phases have occurred in the Chengde-Pingquan region. The first two phases, which formed the superimposed folds, occurred earlier than the Late Triassic (D1) and during the Late Triassic to Early Jurassic (D2). These two phases were followed by three deformation phases that are mainly characterized by thrusting and strike-slip faulting, which strongly modified the large-scale fold interference patterns. Highlights: Multiple shortening phases have occurred in the central part of the Yanshan Orogenic Belt (YOB), North China. Two kilometre-scale arrowhead fold interference patterns are recognized (YOB) and restored. The NW-SE trending F1 folds are refolded by the ENE-WSW F2 folding during the Late Triassic to Early Jurassic. In addition to interlimb angles, the asymmetry of F1 folds can also influence the resulting interference patterns.